Training on Job Satisfaction Analysis and Motivation on the Performance of Car Dealer Emloyes in the Cuty of Palangka Raya - Nahan, Noorjaya; Toendan, Rita Yuanita; Tunjang, Hansly (Jurnal Pengabdian Pancasila (JPP), 2023)
Community service activities with analysis of the job satisfaction system for employees in increasing the sense of comfort and belonging at work are unique activities carried out. This activity was carried out on 63 employees who were registered as actively working. This is to improve management and systems between job satisfaction and worker motivation which can improve performance. By analogy, the results of this service become a reference for business owners in providing policies in the workplace. Implementation of the results of service activities with this analysis really helps workers in expressing and showing job satisfaction and motivation in achieving company targets. Theoretical and practical implications are obtained in the results of this research. Where the theoretical implications show the results that job satisfaction and motivation have a significant effect on the performance of Honda Trio Raya employees in Palangka Raya City. This shows empirical support and strengthens the statement regarding the results of previous studies and statements in the literature that job satisfaction and motivation are indeed influencing factors to improve performance. The practical implications can be seen from the results of hypothesis testing showing that between the two independent variables, the job satisfaction variable has the highest influence on performance compared to other variables. In further service activities, this can be carried out at other dealers by including the work environment and service quality as the basis for the analysis.